Whole exome sequencing identifies novel recurrently mutated genes in patients with splenic marginal zone lymphoma. - Marina Parry; Matthew J J Rose-Zerilli; Jane Gibson; Sarah Ennis; Renata Walewska; Jade Forster; Helen Parker; Zadie Davis; Anne Gardiner; Andrew Collins; David G Oscier; Jonathan C Strefford (PLoS ONE, 2013)
The pathogenesis of splenic marginal zone lymphoma (SMZL) remains largely unknown. Recent high-throughput sequencing studies have identified recurrent mutations in key pathways, most notably NOTCH2 mutations in >25% of patients. These studies are based on small, heterogeneous discovery cohorts, and therefore only captured a fraction of the lesions present in the SMZL genome. To identify further novel pathogenic mutations within related biochemical pathways, we applied whole exome sequencing (WES) and copy number (CN) analysis to a biologically and clinically homogeneous cohort of seven SMZL patients with 7q abnormalities and IGHV1-2*04 gene usage. We identified 173 somatic non-silent variants, affecting 160 distinct genes. In additional to providing independent validation of the presence of mutation in several previously reported genes (NOTCH2, TNFAIP3, MAP3K14, MLL2 and SPEN), our study defined eight additional recurrently mutated genes in SMZL; these genes are CREBBP, CBFA2T3, AMOTL1, FAT4, FBXO11, PLA2G4D, TRRAP and USH2A. By integrating our WES and CN data we identified three mutated putative candidate genes targeted by 7q deletions (CUL1, EZH2 and FLNC), with FLNC positioned within the well-characterized 7q minimally deleted region. Taken together, this work expands the reported directory of recurrently mutated cancer genes in this disease, thereby expanding our understanding of SMZL pathogenesis. Ultimately, this work will help to establish a stratified approach to care including the possibility of targeted therapy.